Development of Leishmania (Mundinia) in guinea pigs - Becvar, Tomas; Padet Siriyasatien; Bates, Paul; Volf, Petr; Sádlová, Jovana (figshare, 2020)
Abstract Background Leishmaniasis is a human and animal disease caused by parasites of the genus Leishmania, which is now divided into four subgenera, Leishmania, Viannia, Sauroleishmania and Mundinia. Subgenus Mundinia, established in 2016, is geographically widely dispersed, its distribution covers all continents, except Antarctica. It consists of 5 species; L. enriettii and L. macropodum are parasites of wild mammals while L. martiniquensis, L. orientalis and an unnamed Leishmania sp. from Ghana are infectious to humans. There is very little information on natural reservoir hosts and vectors for any Mundinia species. Methods Experimental infections of guinea pigs with all five Mundinia species were performed. Animals were injected intradermally with 107 culture-derived promastigotes into both ear pinnae. The courses of infections were monitored weekly; xenodiagnoses were performed at weeks 4 and 8 post-infection using Lutzomyia migonei. The distribution of parasites in different tissues was determined post-mortem by conventional PCR. Results No significant differences in weight were observed between infected animals and the control group. Animals infected with L. enriettii developed temporary lesions at the site of inoculation and were infectious to Lu. migonei in xenodiagnoses. Animals infected with L. martiniquensis and L. orientalis developed temporary erythema and dry lesions at the site of inoculation, respectively, but were not infectious to sand flies. Guinea pigs infected by L. macropodum and Leishmania sp. from Ghana showed no signs of infection during experiments, were not infectious to sand flies and leishmanial DNA was not detected in their tissue samples at the end of experiments at week 12 post-inoculation. Conclusions According to our results, guinea pigs are not an appropriate model organism for studying Mundinia species other than L. enriettii. We suggest that for better understanding of L. (Mundinia) biology it is necessary to focus on other model organisms.